Papilla height in relation to the distance between bone crest and interproximal contact point at single‐tooth implants: A systematic review. Issue Volume 29:Issue S15(2018) (2nd March 2018) - Roccuzzo, Mario; Roccuzzo, Andrea; Ramanuskaite, Ausra
Abstract: Objectives: The aim of this systematic review was to investigate the tooth–implant papilla formation in correlation with the distance between the interproximal bone level and the prosthetic contact point. Material and Methods: A comprehensive search of the current literature (01/01/2000–01/01/2017) was performed to identify human trials that included 10 patients or more, with at least 12 months follow‐up, in need of the replacement of one single tooth in the anterior maxillary region with an implant‐supported single crown. To meet the inclusion criteria, studies had to provide both radiographic and clinical data regarding the distance between the interproximal bone level and the prosthetic contact point. Results: The search yielded 136 records. After evaluation of abstracts and full texts, 12 papers were included in the final review, even though various reference points, for the comparison between the vertical distance and the papilla height, were used. The vertical distance between the interproximal bone level and prosthetic contact point ranged between 2 and 11 mm, and the partial or complete papilla fill (Jemt's score 2–3) ranged between 56.5% and 100% of cases. Conclusion: There is limited evidence that the vertical distance from the base of the interproximal contact point to the crestal bone level seems to affect the interproximal papilla height; that is, the lower is the distance the higher is the percentage of papilla fill. Complete embrasure fill between an implant restoration and the adjacent tooth seems to be correlated with the integrity of the periodontal ligament of the tooth. To reduce the risk of aesthetic failures, interproximal probing on the adjacent teeth should be encouraged before implant placement.